Evolution of microstructure and mechanical properties of D2 tool steel during annealing heat treatment. (2018) - Ramesh, G.; Rahul, R.; Pradeep, M.; Sreehari, P.; Kumar, S. Ramesh
Abstract: In the present work, the effect of annealing soling time on evolution of microstructure and mechanical properties of D2 tool was investigated. The increase in soaking time during annealing process causes the morphology of carbides transform from irregular shape to nearly rounded shape and distributed uniformly in a pearlite matrix. The increased amountof carbide dissolution during annealing resulted in enhancement ductility and decrement of strength of D2 tool steel. The study indicates that desirable properties of D2 Steel could be obtained by judicious selection of annealing cycle.